Measures for the assessment of stressful life events in the Spanish adult population: A systematic review. - Motrico, Emma; Rodero-Cosano, María Luisa; Álvarez-Gálvez, Javier; Salinas-Pérez, Jose Alberto; Moreno-Peral, Patricia (Anales de Psicología / Annals of Psychology, 2017)
Objective The aim of this research is to identify and analyze the measures for the assessment of stressful life events created/adapted for its use in Spanish adult population, published in national and international literature, with a focus on psychometric properties and its association with health measures. Methods A systematic review was carried out to identify all instruments identified through searches of MEDLINE; ProQuest Health and Medical Complete; ProQuest Psychology Journals; PsycARTICLES; PsycINFO; Psicodoc; OpenSIGLE from inception until 31 January 2016. Two independent researchers assessed the eligibility criteria of all articles, subtracted data and assessed its psychometric properties. Results Twelve measures, which satisfied the inclusion criteria, were selected. The measures showed a large heterogeneity. Most of them did not include any information on its psychometric properties or needed to provide further data, since a few of them assessed its test-retest stability and/or internal structure. The questionnaires created or adapted by González de Rivera y Morena (1983), Sandín y Chorot (1987), Fernández y Mielgo (1992), Gracia y Herrero (2004), and Motrico et al. (2013) showed significant associations with health variables. Discussion Further research is needed to clarify the association of these instruments with mental and physical health measures, which would facilitate its clinical application. These results are very useful in order to select a measure for the assessment of stressful life events in clinical practice and research in Spain.